Flipped classrooms: Action research to improve practice within an HE nursing context - Matt Smith; Amanda Turner (Educational Futures, 2022)
This article explores the importance of careful design when using a flipped classroom to support the learning of an Anatomy and Physiology module for year one undergraduate nursing students. It is argued that an online platform of well-designed materials and activities will effectively support the retention of key information, thus increasing the time in synchronous classrooms for discussion, debate and assimilation of higher-order knowledge. An action research approach was taken in order to explore this particular issue underpinned by qualitative methodology. Data was gathered via a questionnaire from a group of students, and through an interview with an experienced colleague. Through careful analysis of the data, results from the research showed a positive reaction to the newly designed flipped classroom. The resource was easy to access and navigate and had increased a more self-directed approach to learning content. This had a positive impact on self-efficacy, as students reported having more belief in their ability to learn independently. As we move more towards the implementation of more flipped classrooms, further research exploring different elements for successful engagement with this resource will be inevitable. What this research has provided is a clear model for effective flipped classrooms which can be used as a basis for future developments.